Knowledge Management in Local Governments: A Boost or a Brake on Productivity? - Montano, Santos; Montano, Julio; Quiroz, Baldemar; Alcahuaman, Jeny; Espejo-Chacón, Luis Fernando; García, Luis Alberto Torres (Journal of Ecohumanism, 2024)
This study analyzes the impact of knowledge management on the productivity of a local government, to determine whether it acts as a boost or a brake on institutional performance. Using a quantitative approach, a non-experimental design and an explanatory level, 119 municipal workers were evaluated using validated and reliable instruments. The dimensions of knowledge detection, capture and development were examined, applying Spearman correlation and ordinal regression. The results revealed a positive and significant correlation between knowledge management and productivity (Rho = 0.810, p = 0.000), indicating that effective management is associated with higher levels of productivity. The regression model showed that knowledge management explains 66.2% of the variability in productivity, reflecting an important influence. However, areas for improvement were identified, especially in knowledge detection, where significant levels of inefficiency and regularity were perceived. It was concluded that knowledge management in the local government studied acts both as a boost and a brake on productivity. It is recommended to implement strategies that strengthen detection, capture and knowledge development practices, in order to optimize operational efficiency and offer higher quality services to the population.